EFFICACY OF PUBOVAGINAL SLING USING FASCIA LATA FOR TREATMENT OF URODYNAMIC STRESS INCONTINENCE IN FEMALES: Effects of Pubovaginal Sling - Alia, Asma; Ahmed, Faizan; Burney, Muhammad Rehan (Pakistan Armed Forces Medical Journal, 2009)
Objective: To evaluate results of pubovaginal sling surgery for the treatment of urodynamic stress incontinence in females. Study Design: Descriptive study. Place and Duration of Study: This study was carried out in Pakistan Naval Services Shifa, Karachi & Armed Forces Institute of Urology,Rawalpindi from February 1997 to February 2004. Patients and Methods: Thirty two Pubovaginal sling operations using fascia lata were performed at Pakistan Naval Ship Shifa, Karachi and Armed Forces Institute of Urology, Rawalpindi in females having severe urodynamic stress incontinence. The inclusion criteria was women with stable bladder, having post void residual urine (PVRU) <100 ml and P det 720 cm of water. Patients with detrusor overactivity, impaired detrusor function and marked cystocele were excluded from the study. The procedure involves placing a band of sling material using fascia lata directly under the bladder neck, which acts as a physical support to prevent bladder neck and urethral descent during physical activity. All patients were evaluated postoperatively by clinical examination, PVRU, Peak flow rate on uroflowmetry and urodynamic assessment. Results: Mean patients age was 46.5 years (range 27-68) and mean parity was 6 (range 0-10). Follow up was completed in all 32 patients over a mean follow-up period of 26 months (range 3-38). Overall success rate (completely cured and partially cured) was 84%. De. novo detrusor over activity was observed in 25% patients, while 2 patients underwent undo operation for urinary obstruction. Conclusion: Pubovaginal sling surgery is the first line surgical treatment for all types of urodynamic stress incontinence.